EFEKTIFITAS PERAN PIMPINAN DALAM PELAKSANAAN GERAKAN MASYARAKAT HIDUP SEHAT UNTUK MENINGKATKAN KESEHATAN MASYARAKAT - Florentina Kusyanti; Ima Kristina Yulita (Universitas Respati Yogyakarta, 2020)
Background: Individual health is everyone's needs and rights, but for health-related issues it is the responsibility of all levels of Indonesian society both private and Government agencies. On the results of disease evaluation from the Ministry of Health of the Republic of Indonesia concerning the development of diseases that there is a changefrom infectious diseases to non-communicable diseases caused by the lack of population activity by 26.1%, drinking alcohol 4.6%, consuming less vegetables and fruit by 93.5%.A healthy village is a village that is clean and organized and the level of understanding of health for the community is good and wants to carry out activities that support to improve the health of all people in the community.Objective: to find out how effective the leadership's role is in implementing the movement for a healthy lifestyle.Methods: The case study research design was qualitative, for the research technique used was a pusposive sampling technique. Data collection was carried out by 2 graduate students by means of in-depth interviews and documentation studies. The main informants were the lurah pak, and the 6 angarang triangulation information consisting of from the village midwife, the head of the village PKK, the head of the health cadre, and 3 hamlet heads in the village of mertoyudanResults: observation and interviews with informants that the role of leaders in the implementation of the movement for healthy living is not yet optimal, because the village head has invited to do the germas but subordinates have not carried out the maximum and have not given concrete examples of implementation that can be emulated by the community in carrying out the community movement for healthy living the level of knowledge is good.Conclusion : the role of leaders in the implementation of the movement for healthy living is not yet optimal, because the village head has invited to do the germas but subordinates have not carried out the maximum and have not given concrete.